2006
DOI: 10.1016/j.jhealeco.2005.11.002
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the length of stay and effectiveness of treatment for hip fracture patients in Japan: Evaluation of the 2002 revision of the medical service fee schedule

Abstract: The length of hospital stay and effectiveness of medical treatment are analyzed using data of patients hospitalized due to hip fractures of four hospitals in Japan. The influence of the Revision of the Medical Service Fee Schedule in April, 2002, is evaluated, and factors which may have affected the length of stay and effectiveness of treatment (walking ability upon departure from the hospital) are also analyzed by a newly developed simultaneous equation model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 8 publications
(5 reference statements)
0
10
0
Order By: Relevance
“…Furthermore, LOS in acute hospital care and LOS including days in rehabilitation units were prolonged for those patients. Earlier studies have focused on the patients prefracture medical condition related to mortality (Parker et al, 2000;Roche et al, 2005) and/or LOS (Beaupre et al, 2006;Nawata et al, 2006). In this study no significant difference was found between patients characteristics at admission compared to patients treated at an orthopaedic department and patients treated at other departments or between patients in the control and intervention groups.…”
Section: Discussionmentioning
confidence: 57%
“…Furthermore, LOS in acute hospital care and LOS including days in rehabilitation units were prolonged for those patients. Earlier studies have focused on the patients prefracture medical condition related to mortality (Parker et al, 2000;Roche et al, 2005) and/or LOS (Beaupre et al, 2006;Nawata et al, 2006). In this study no significant difference was found between patients characteristics at admission compared to patients treated at an orthopaedic department and patients treated at other departments or between patients in the control and intervention groups.…”
Section: Discussionmentioning
confidence: 57%
“…In Japan, medical costs are measured by points rather than yen, and medical institutes are paid 10 yen per point [52]. The average and standard deviations (SD) were 13,672 and 39,576 points, respectively, and the total cost was 1558 million points.…”
Section: Distribution Of Medical Costs For All Casesmentioning
confidence: 99%
“…10 yen per point is payed to medical institutes. For details, see Nawata et al [46] In the national survey [33], the total payment to hospitals, clinics, and pharmacies was 36.5 trillion yen, and the medical expenditure for diabetes was 3.3% of this total; this implies that diabetes might be a much costlier disease than generally thought.…”
Section: Medical Paymentsmentioning
confidence: 99%